PERILAKU BERAGAMA DAN ETOS KERJA MASYARAKAT PESISIR DI KELURAHAN PENGGOLI KECAMATAN WARA UTARA KOTA PALOPO - Thaha, Hamdani; Ilyas, Muhammad (IAIN Palopo, 2016)
AbstractThis study discussed the religious attitude and worked ethos of coastal communities in thePenggoli (studies on the clumps of Lawatu). The purpose of this study is to determine thepattern of religious behavior and its relationship with a work ethic of Lawatu societies. The datawere collected through observation, documentation, and structured-interviews. The interviewswere conducted in semi-structures by selecting the informant utilizing a purposive samplingtechnique. The findings showed that: 1) Lawatu societies who live in Penggoli are devoutreligious believers, but they also still maintain ancestorsâ cultures transformed into religiousrituals. Many rituals that have become religious traditions are still often conducted by Lawatusocieties, for examples: Mabbaca-baca, Massio-sio, and Mammaulu. 2) They have livesprinciples in running their activities, especially in civic lives and subsistences. The principles arein the forms of Mabbulo Sibatang, Pakkareso, Mapanre Lima, Sipakatongeng.